New lights in the valley : the emergence of UAB - McWilliams, Tennant S., 1943- (University of Alabama Press, 2007)
A scholarly narrative of UAB from its nascent beginnings through the mid 1990's. While the economy and culture of the post-World War II South changed from an era of material capital (e.g., cotton and iron ore) to a period of social capital (intellectual development and networked approaches to social change), one of the most important components of urban life, the university, emerged as both a creator and a reflector of such modernization. This is the case with Birmingham and its youthful institution of higher learning, the University of Alabama at Birmingham.